2016
DOI: 10.3389/fphar.2016.00418
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotanshinone I Attenuates Atherosclerosis in ApoE-Deficient Mice: Role of NOX4/NF-κB Mediated Lectin-Like Oxidized LDL Receptor-1 (LOX-1) of the Endothelium

Abstract: Dihydrotanshinone I (DHT) is a natural compound extracted from Salvia miltiorrhiza Bunge which has been widely used for treating cardiovascular diseases. However, its role in atherosclerosis remains unclear. In this study, the effect of DHT on atherosclerosis were investigated using apolipoprotein E-deficient (ApoE-/-) mice and endothelial cells. In lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells (HUVECs), DHT (10 nM) decreased lectin-like ox-LDL receptor-1 (LOX-1) and NADPH oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…), and overexpress LOX‐1 in ECs (Zhao et al . ). This pro‐inflammatory predisposition might exaggerate the damage of an acute lung injury.…”
Section: Vascular Function In Dyslipidaemiamentioning
confidence: 97%
“…), and overexpress LOX‐1 in ECs (Zhao et al . ). This pro‐inflammatory predisposition might exaggerate the damage of an acute lung injury.…”
Section: Vascular Function In Dyslipidaemiamentioning
confidence: 97%
“…A recent study [88] from Chen's laboratory has shown that dihydrotanshinone attenuates diet-induced atherosclerosis in ApoE -/mice. The underlying mechanism is related to blockade of the NOX4 (NADPH oxidase 4)/ROS (reactive oxygen species)/NF-κB/LOX-1 signaling pathway in LPS-stimulated human endothelial cells and subsequent oxLDL endocytosis and monocyte adhesion to endothelial cells [88] . Dihydrotanshinone also inhibits proliferation, migration and tube formation in endothelial cells, thereby inhibiting angiogenesis [89] .…”
Section: Dihydrotanshinonementioning
confidence: 99%
“… 41 reported that blockade of TNF-α-induced ROS by NOX4 siRNA suppressed the TNF-α-induced ICAM-1 expression and subsequent monocyte adhesion to human aortic endothelial cells. Also our previous study showed that NOX4 plays an important role in the process of atherosclerosis 42 . In the current research, we found that the knockdown of NOX4 by siRNA significantly inhibited the TNF-α-induced ROS production and ICAM-1 expression at both protein and mRNA levels, as well as the THP-1 – HUVEC adhesions.…”
Section: Discussionmentioning
confidence: 91%